Reliability verification of a vision-based dynamic displacement measurement for system identification. Issue 191 (August 2019) - Kim, Hongjin; Shin, Seunghoon
Abstract: In this paper, dynamic experiments of various amplitudes with a broad band of frequencies were carried out using a shaking table in order to validate the wide-range reliability of a vision-based displacement measurement system. In addition, the dynamic characteristics of a multiple-degree-of-freedom model structures were estimated using the vision-based measurement method. As a result of error analysis through comparison with a laser displacement sensor (LDS), it was determined that the accuracy of dynamic displacement measurement by the camcorder in the vision-based system is affected by the frequency of the measurement object. From these results, it is judged that the CMOS sensor type has the rolling shutter effect when the velocity between the model structure and the camcorder is high. The accuracy of dynamic characteristics estimation was determined by comparing the dynamic characteristics estimated using the LDSs and the accelerometers. The vision-based measurement system using the camcorder in both time domain and frequency domains showed very similar results to the existing LDS and accelerometer measurements. Highlights: The reliability of a vision-based displacement measurement system was verified through the shaking table tests. The case of the measurement object was specifically subdivided. The influence of the dynamic motion level of the object on the measurement performance is shown in detail.